Characterization of Escherichia coli obtained from patients undergoing peritoneal dialysis and diagnosed with peritonitis in a Brazilian centre - Dias, Regiane C B [UNESP]; Vieira, Melissa A. [UNESP]; Moro, Ana C. [UNESP]; Ribolli, Danilo F M [UNESP]; Monteiro, Aydir C M [UNESP]; Camargo, Carlos H.; Tiba-Casas, Monique R.; Soares, Flávia B; Dos Santos, Luis F.; Montelli, Augusto C. [UNESP]; da Cunha, Maria de Lourdes R de S [UNESP]; Barretti, Pasqual [UNESP]; et al. (Microbiology Society, 2019)
Purpose. This study aimed to characterize 27 Escherichia coli isolates obtained from peritoneal dialysis (PD)-related peritonitis that occurred at the University Hospital of Botucatu Medical School, Brazil, between 1997 and 2015.Methodology. These isolates were characterized regarding the occurrence of 22 virulence factor-encoding genes, antimicrobial resistance and biofilm production. We then evaluated whether these factors influenced the clinical outcome.Results. Over an 18-year period, 726 episodes of PD-related peritonitis were diagnosed, with 27 of them (3.7 %) being due to E. coli. The majority of the isolates were classified in phylogroups B1 (33.3 %), B2 (30.0 %) or F (18.0 %). fimH (100.0 %), ompT (66.7 %) and irp2 (51.9 %) were the most prevalent genes, while papA, papC, iha, sat, irp2, iucD, ireA, ibe10, ompT and kpsMTII were significantly more prevalent among isolates belonging to phylogroups B2 and F (P<0.05). Non-susceptibility to quinolones was detected in six isolates, which harboured chromosomal and/or plasmid-mediated quinolone resistance determinants, while two CTX-M extended-spectrum β-lactamase-producing E. coli were identified. Virulence factor-encoding genes (alone or in combination) and antimicrobial resistance were not associated with non-resolution outcomes. However, there was a trend for the ability to produce biofilm to be associated with treatment failure, although this association was not statistically significant.Conclusion. The E. coli isolates were heterogeneous in terms of the features investigated, and were susceptible to most of the antimicrobial drugs tested, despite the unsuccessful treatment observed in more than 50.0 % of the patients. Studies including more cases could help to clarify if biofilm production can influence the outcome in patients with PD-related peritonitis.
Keywords: antimicrobial resistance; Escherichia coli; peritoneal dialysis; peritonitis; virulence factors